Trickle-Bed Bioreactors for Acetogenic H2/CO2 Conversion - Steger, Franziska; Ergal, İpek; Daubek, Armin; Loibl, Nadine; Rachbauer, Lydia; Fuchs, Werner; Rittmann, Simon K.-M. R.; Bochmann, Günther (Frontiers in Energy Research, 2022)
Acetic acid is an essential industrial building block and can be produced by acetogenic bacteria from molecular hydrogen (H2) and carbon dioxide (CO2). When gasses are supplied as substrates, bioreactor design plays an important role for their availability. Trickle-bed bioreactors (TBs) have an enhanced gas-to-liquid mass transfer and cells remain in the system by forming a biofilm on the carriers. So far, TBs have been investigated extensively for bio-methanation processes, whereas studies for their use in acetic acid production are rare. In this study, we evaluated the reproducibility of two parallel TBs for acetic acid production from H2:CO2 (= 70:30) by a mixed culture with a gas flow rate of 3.8 mL min−1 and a medium flow rate of 10 mL min−1. Additionally, the effect of glucose addition during the starting phase on the resulting products and microbial composition was investigated by setting up a third TB2. Partial medium exchanges to decrease the internal acetic acid concentration (AAC) combined with recycling of withdrawn cells had a positive impact on acetic acid production rates with maxima of around 1 g L−1 d−1 even at high AACs of 19–25 g L−1. Initial glucose addition resulted in the accumulation of unwanted butyric acid up to concentrations of 2.60 ± 0.64 g L−1. The maximum AAC of 40.84 g L−1 was obtained without initial glucose addition. The main families identified in the acetogenic TBs were Peptococcaceae, Ruminococcaceae, Planococcaceae, Enterobacteriaceae, Clostridiaceae, Lachnospiraceae, Dysgonomonadaceae and Tannerellaceae. We conclude that a TB is a viable solution for conversion of H2/CO2 to acetate using an anaerobic enrichment culture.